2022
DOI: 10.2132/personality.30.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Development of Revised Japanese Version of Generativity Scale (JGS-R) and Investigation of its Reliability and Validity

Abstract: Recently, many researchers have focused on generativity as a psychosocial task in old age as well as middle age. In this study, we developed a revised Japanese version of the Generativity Scale (JGS-R), which measures multiple aspects of generativity among elderly people, and investigated its reliability and validity.e items were constructed based on the Japanese version of the Generativity Scale (Ohba et al., 2013). JGS-R was administered to 1,393 elderly people living in urban areas. Exploratory factor analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 8 publications
0
10
1
Order By: Relevance
“…The analysis items were as follows: (1) willingness to continue volunteering (agree, somewhat agree, somewhat disagree, and disagree); (2) fear of COVID‐19 (not afraid, afraid, and very afraid); (3) mental and physical health: subjective sense of health (good or poor), mental health (good or poor, WHO‐5 score range 0–25: if the crude score was less than 13 points based on the cut‐off point of the scale, or if any of the five items was answered as 0 or 1 point, mental health was defined as poor), a group of items related to factors for continuing volunteer activities that were mentioned in previous studies; (4) activity satisfaction (satisfied, somewhat satisfied, neither satisfied nor unsatisfied, somewhat unsatisfied, and unsatisfied); (5) generational inheritance interest (subscale in Revised Japanese Version of Generativity Scale by Murayama et al ., 31 four items, six‐point scale, score range 0–20, with higher scores indicating greater interest); (6) awareness of contribution to the next generation; (7) personal growth; (8) connection through activities; (9) understanding of the purpose and significance of activities; (10) attachment to activities; (11) age; and (12) sex.…”
Section: Methodsmentioning
confidence: 99%
“…The analysis items were as follows: (1) willingness to continue volunteering (agree, somewhat agree, somewhat disagree, and disagree); (2) fear of COVID‐19 (not afraid, afraid, and very afraid); (3) mental and physical health: subjective sense of health (good or poor), mental health (good or poor, WHO‐5 score range 0–25: if the crude score was less than 13 points based on the cut‐off point of the scale, or if any of the five items was answered as 0 or 1 point, mental health was defined as poor), a group of items related to factors for continuing volunteer activities that were mentioned in previous studies; (4) activity satisfaction (satisfied, somewhat satisfied, neither satisfied nor unsatisfied, somewhat unsatisfied, and unsatisfied); (5) generational inheritance interest (subscale in Revised Japanese Version of Generativity Scale by Murayama et al ., 31 four items, six‐point scale, score range 0–20, with higher scores indicating greater interest); (6) awareness of contribution to the next generation; (7) personal growth; (8) connection through activities; (9) understanding of the purpose and significance of activities; (10) attachment to activities; (11) age; and (12) sex.…”
Section: Methodsmentioning
confidence: 99%
“…Since 2002, dredged soil from the Kanmon Waterway has been discharged into the S-3 area. In 2011, the revetment height of the S-3 area was raised to DL + 12.0 m using mechanically dewatered clay (MDC) lumps created by removing pore water from the dredged clay [3]. This expansion increased the capacity of the S-3 area by approximately 3,100,000 m 3 , with an additional 940,000 m 3 of MDC lumps used for extra fill on the revetments [4].…”
Section: Outline Of S-3 Area Of Shinmoji-oki Disposal Pondmentioning
confidence: 99%
“…This expansion increased the capacity of the S-3 area by approximately 3,100,000 m 3 , with an additional 940,000 m 3 of MDC lumps used for extra fill on the revetments [4]. Overall, the volume available for discharge into the pond was increased by approximately 4 million m 3 . Figure 2 provides a visual representation of these changes.…”
Section: Outline Of S-3 Area Of Shinmoji-oki Disposal Pondmentioning
confidence: 99%
“…In this study, we explored the concept of generativity, which pertains to the transmission of experiences and knowledge from older to younger generations. Erikson [ 3 ] defined generativity as the interest in nurturing and guiding the next generation, primarily through the act of parenting [ 4 ]. However, recent trends such as increased life expectancy and delayed marriages have led to a broader interpretation of generativity as a psychological and social issue encompassing adulthood and old age [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, recent trends such as increased life expectancy and delayed marriages have led to a broader interpretation of generativity as a psychological and social issue encompassing adulthood and old age [ 5 ]. Indeed, research involving older adults has demonstrated that those with higher levels of generativity tend to experience greater life satisfaction [ 6 , 7 ] and are more likely to participate in local parenting support initiatives [ 4 ]. Generativity comprises the following elements: (1) generative action, which includes specific actions like sharing personal experiences; (2) generative concern, which signifies an interest in engaging with younger generations and in creative activities; and (3) generative accomplishment, which conveys a sense of societal contribution and involvement in passing experiences to younger generations [ 4 ].…”
Section: Introductionmentioning
confidence: 99%